Teaching Students to Interpret Religious Poetry (and to Expand their Avenues of Thinking) - Jacobson, Rolf A. (Teaching theology and religion, 2004)
Teaching religion and theology requires interpretation of the vast corpus of religious poetry that is found in every religious tradition, but students are generally ill-equipped to interpret this material. Therefore teachers would do well to teach the students how to interpret religious poetry. This article discusses some of the challenges of teaching this material to students and discusses techniques and exercises that have been found useful in teaching students how to navigate the terrain of religious poetry.